High-voltage lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof
Lithium iron manganese phosphate nanoparticles are prepared by mixing phosphate compounds, manganese salts and iron salts in a specific molar ratio under inert atmosphere conditions, and adding high boiling point organic solvents and lithium hydroxide solutions, through ultrasonic treatment and condensation reflux reaction, and The cathode material is formed by calcining at high temperatures, which solves the problem of platform voltage reduction caused by stress and strain during high-rate discharge of the lithium iron manganese phosphate cathode material, achieving high energy density and excellent rate performance.
Patent Information
- Application Number
- CN202411887520.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the high-speed discharge process of lithium manganese iron phosphate, the internal stress strain of the particles is caused by lithium heterogeneity, resulting in a decrease in the platform voltage and the discharge voltage of Mn3+ deviating from the original working voltage of the redox reaction.
Under a preparation method, under the condition of inert atmosphere, soluble phosphate root compounds, soluble binary manganese salt and soluble binary iron salt are mixed according to specific Murbis, adding high -boiling organic solvents and lithium hydroxide solutions, through ultrasound treatment and The condensation reflux reaction obtains lithium nano particles of manganese iron phosphate, and the positive electrode material is formed at high temperature.
The manganese-lithium nano particles prepared through this method have a uniform rice granular structure with a particle size of 30-100nm, high crystallinity, high purity, can effectively suppress stress strain, maintain high discharge voltage, increase the energy density and magnification of the battery, increase the energy density and magnification of the battery performance.
Smart Images

Figure CN119330328A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a high-voltage lithium manganese iron phosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] As the core energy storage device in the field of modern science and technology, lithium-ion batteries play an irreplaceable supporting role in the conversion and storage of modern energy. With the rapid development of the clean energy storage industry and electric vehicles, the market has put forward higher requirements on the energy density, cycle life, safety and charging speed of lithium-ion batteries. As one of the key materials in the lithium-ion battery system, the positive electrode material has received widespread attention. Among various positive electrode materials, olivine-structured lithium manganese iron phosphate has the advantages of being non-toxic, pollution-free, safe, low-cost, high energy density and long cycle life, and has become an important candidate for the next generation of lithium-ion battery positive electrodes.
[0003] Compared with the commercialized lithium iron phosphate, lithium iron manganese phosphate has lower electronic / ionic conductivity, lower compaction density, more complex phase transition mechanism, structural distortion caused by Jahn-Teller effect and Mn dissolution. In order to solve these problems, people have proposed a series of improvement measures, including new synthesis methods, carbon coating and modification, bulk doping, surface modification and preparation of spherical particles. These methods have accelerated the lithium diffusion kinetics of lithium iron phosphate positive electrode to a certain extent, improved the material's tapping and compaction density, stabilized the lattice structure during lithium insertion and extraction, and limited the dissolution of Mn. However, there is a generally overlooked defect in the lithium iron phosphate positive electrode, that is, during high-rate discharge, the inhomogeneity of lithium inside the particles will produce obvious stress and strain, resulting in a more serious platform voltage reduction phenomenon, which makes Mn 3+ The discharge voltage deviates from the original Mn 2+ / Mn 3+ The working voltage of the redox reaction; the inventors of the present application have found that this stress-strain will be alleviated to a certain extent as the size of the lithium manganese iron phosphate particles is greatly reduced.
[0004] At present, the main method for synthesizing small-sized lithium manganese iron phosphate particles is the liquid phase method, and its liquid phase system can be divided into pure water, organic or non-aqueous solvents, and mixed solvents of water and organic matter. Among them, the pure water system mainly utilizes a high-temperature and high-pressure hydrothermal environment to promote the dissolution and reaction of various raw materials (such as phosphorus source, iron source, manganese source, etc.), which has the advantages of short synthesis cycle, low cost, and high product purity. However, in order to obtain smaller particles, this system usually requires the addition of a large amount of auxiliary agents or the use of microwaves and other means, and the minimum particle size that can be achieved is still limited; the organic or non-aqueous solvent system is developed based on the pure water system, and the particle product is refined by the regulation of the morphology of organic or non-aqueous solvents. Compared with the pure water system, smaller particles can be obtained in this system, but since the solubility of the initial raw materials in organic or non-aqueous solvents will be greatly reduced, the single synthesis yield will be significantly reduced; the water and organic mixed solvent system combines the advantages of the previous two liquid phase systems, which can not only increase the solubility of the initial raw materials, thereby increasing the yield of a single synthesis, but also obtain small-scale particles. Therefore, it is widely used, but this system still relies on a high-pressure closed reaction environment, has high requirements for equipment, and has low safety. Summary of the invention
[0005] The purpose of the present invention is to provide a high-voltage lithium manganese iron phosphate positive electrode material and a preparation method and application thereof, so as to solve the problems raised in the background technology.
[0006] In order to achieve the above object, the present invention provides the following technical solutions: The first aspect of the present invention provides a method for preparing a high voltage lithium manganese iron phosphate positive electrode material, comprising the following steps: 1) Under inert atmosphere, a soluble phosphate compound, a soluble divalent manganese salt and a soluble divalent iron salt are added to deionized water at a molar ratio of P: (Mn+Fe) = 1:1, stirred until completely dissolved, and then an appropriate amount of an antioxidant is added to obtain a mixed solution with a total metal salt molar concentration of 1-3 mol / L; 2) adding 1-10 times the volume of deionized water into the mixed solution obtained in step 1) and subjecting it to ultrasonic treatment; 3) placing the mixed solution obtained in step 2) in a normal pressure condensation reflux reactor, slowly adding a lithium hydroxide solution with a concentration of 1-3 mol / L into the reactor, stirring at a rate of 50-500 rpm, heating the reactor to 140-180°C at a heating rate of 5-15°C / min, keeping the temperature and condensing reflux for reaction for 2-12 hours, and after the reaction is completed, filtering out the solid product, washing, and drying to obtain lithium manganese iron phosphate nanoparticle powder; 4) The lithium manganese iron phosphate nanoparticle powder prepared in step 3) is dispersed with a carbon source in a solvent, subjected to ultrasonic treatment, spray-dried, and calcined at a high temperature under the protection of an inert gas to obtain a lithium manganese iron phosphate positive electrode material.
[0007] Preferably, the phosphate salt in step 1) is one or more of diammonium hydrogen phosphate, ammonium dihydrogen phosphate or phosphoric acid, the soluble divalent manganese salt is one or more of manganous sulfate, manganous nitrate or manganous chloride, and the soluble divalent iron salt is one or more of ferrous sulfate, ferrous nitrate or ferrous chloride.
[0008] Preferably, in step 1), the molar ratio of Mn:Fe provided by the soluble divalent manganese salt and the soluble divalent iron salt is 1-4:1.
[0009] Preferably, the antioxidant in step 1) is ascorbic acid or citric acid, and the added amount of the antioxidant is 0.5-5% of the total mass of the metal salt.
[0010] Preferably, the boiling point of the high boiling point organic solvent in step 2) should be higher than the insulation temperature in step 3).
[0011] More preferably, the high boiling point organic solvent in step 2) is one of ethylene glycol, propylene glycol, diformate or sulfolane.
[0012] Preferably, the ultrasonic treatment time in step 2) is 3-15 min, and the ultrasonic frequency is 30-50 KHz.
[0013] Preferably, in step 3), lithium hydroxide solution is added to the mixed solution at a molar ratio of Li:P = 3-3.15:1, and the addition rate of the lithium hydroxide solution is 1-10 mL / min.
[0014] Preferably, in step 4), the carbon source is one of glucose, sucrose, phenolic resin or starch, the mass of the carbon source is 1%-20% of the mass of the lithium manganese iron phosphate nanoparticle powder, and the solvent is water or ethanol.
[0015] Preferably, in step 4), the ultrasonic treatment time is 10-60 min, the ultrasonic frequency is 30-50 KHz, the high temperature calcination temperature is 600-800° C., and the calcination time is 4-8 h.
[0016] The principle of the preparation method of the present invention is: in the initial stage of the reaction, since the solvent system is a mixed solution of water and an organic solvent, the reaction materials first form a ferromanganese phosphate compound intermediate. In this stage, by adjusting the ratio of water to the organic solvent, the concentration of the reactants, the heating rate, the stirring intensity and other parameters, the nucleation and growth rate of the ferromanganese phosphate compound intermediate can be flexibly adjusted, and then the particle size and morphology of the final product can be regulated; in the subsequent condensation reflux reaction stage, the reaction temperature of the system is relatively higher, and the high-temperature solvent thermal effect can improve the penetration ability of lithium ions in the solution, prompting them to be embedded in the ferromanganese phosphate compound intermediate to obtain lithium iron manganese phosphate particles, and further promote crystal maturation and improve crystallinity, and finally obtain small-scale lithium iron manganese phosphate nanoparticles with excellent quality.
[0017] The second aspect of the present invention provides a high-voltage lithium iron manganese phosphate positive electrode material prepared by the above-mentioned preparation method.
[0018] A third aspect of the present invention provides an application of a high-voltage lithium iron manganese phosphate positive electrode material in a positive electrode of a lithium-ion battery.
[0019] Based on this, the beneficial effects of the present invention are: 1. The preparation method of the present invention uses a mixed solvent of deionized water and a high-boiling point organic solvent as a carrier in the reaction process. On the one hand, it effectively improves the solubility of each reaction raw material and increases the yield of lithium iron manganese phosphate nanoparticles per unit volume; on the other hand, the synthesis process of lithium iron manganese phosphate nanoparticles can be carried out under normal pressure, which reduces equipment cost and operation difficulty. The synthesis process is visual throughout, and the safety and reliability are higher; 2. The present invention does not open the condensation reflux system before the reaction temperature of the system reaches a preset value, so that the water in the initial mixed solvent system is completely evaporated into the atmosphere during the gradual heating process to achieve separation. Therefore, when the reaction enters the termination stage, the reaction solvent system will be converted into a single organic solvent, which is convenient for solvent recovery and reuse through a simple fractionation process, significantly reducing production costs, and also helping to enrich the lithium-containing waste liquid and improve the efficiency of resource utilization; 3. The lithium iron manganese phosphate nanoparticles obtained by the preparation method of the present invention are in the shape of rice grains, with a particle size of nanometer scale and uniform distribution, good crystallinity, high purity, and no obvious growth during high-temperature sintering. Therefore, the secondary particles of the lithium iron manganese phosphate positive electrode material synthesized using it as a precursor are in the shape of microspheres and porous morphology, with good wettability with the electrolyte, high purity, uniform carbon layer coating, and the primary particle size is consistent with the nanoparticle precursor. The small-sized nanoparticles can not only effectively inhibit the occurrence of stress and strain during the discharge process, maintain the high discharge voltage of the positive electrode material, thereby improving the energy density of the battery, but also shorten the path of lithium ion transmission, effectively shorten the distance for lithium ions to diffuse from the surface to the center of the bulk phase, reduce the charge and discharge polarization, and effectively improve the discharge specific capacity and rate performance of the lithium iron manganese phosphate positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 XRD patterns of lithium iron manganese phosphate nanoparticles LFMP-A1, LFMP-A2, LFMP-A3, and LFMP-B1 in Example 1, Example 2, Example 3, and Comparative Example 1; Figure 2 This is a SEM image of the lithium iron manganese phosphate nanoparticles LFMP-A1 prepared in Example 1; Figure 3 This is a SEM image of the lithium iron manganese phosphate nanoparticles LFMP-B1 prepared in Comparative Example 1; Figure 4 XRD diagrams of lithium iron manganese phosphate positive electrode materials LFMP / C-A1 and LFMP / C-B1 in Example 1 and Comparative Example 1; Figure 5 This is a SEM image of the lithium iron manganese phosphate positive electrode material LFMP / C-A1 prepared in Example 1; Figure 6 This is a SEM image of the lithium iron manganese phosphate positive electrode material LFMP / C-B1 prepared in Comparative Example 1; Figure 7 The charge and discharge curves of test battery 1 and test battery 2 at 2C rate; Figure 8 The figure is the rate performance diagram of test battery 1 and test battery 2. DETAILED DESCRIPTION
[0021] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The technicians in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention. In the following examples, reagents and instruments not specifically described are all commercially available, and experimental operations not specifically described are implemented according to the manufacturer's instructions or conventional techniques in the field. Unless otherwise defined, all professional and scientific terms used in the text have the same meanings as those familiar to those skilled in the art. In addition, any method and material similar to or equal to the recorded content can be applied to the present invention; the endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article; the present invention provides a method for preparing a high-voltage lithium manganese iron phosphate positive electrode material, comprising the following steps: 1) Under inert atmosphere conditions, a soluble phosphate compound, a soluble divalent manganese salt and a soluble divalent iron salt are added to deionized water at a molar ratio of P: (Mn + Fe) = 1:1, stirred until completely dissolved, and then an appropriate amount of an antioxidant is added to obtain a mixed solution with a total metal salt molar concentration of 1-3 mol / L, wherein the molar ratio of Mn:Fe provided by the soluble divalent manganese salt and the soluble divalent iron salt is 1-4:1; 2) adding 1-10 times the volume of deionized water into the mixed solution obtained in step 1), and ultrasonically treating at a frequency of 30-50 KHz for 3-15 min; 3) placing the mixed solution obtained in step 2) in a normal pressure condensation reflux reactor, slowly adding a lithium hydroxide solution with a concentration of 1-3 mol / L into the reactor at a rate of 1-10 mL / min, stirring thoroughly at a rate of 50-500 rpm, heating the reactor to 140-180°C at a heating rate of 5-15°C / min, keeping the temperature and condensing the reflux reaction for 2-12 hours, filtering out the solid product after the reaction, washing and drying, and obtaining lithium manganese iron phosphate nanoparticle powder, wherein the molar ratio of Li in the lithium hydroxide solution to P in the mixed solution is 3-3.15:1; 4) The lithium manganese iron phosphate nanoparticle powder prepared in step 3) and 1%-20% of the carbon source by weight are dispersed in a solvent, ultrasonically treated at a frequency of 30-50 KHz for 10-60 min, spray-dried, and calcined at 600-800°C for 4-8 h under the protection of an inert gas to obtain a lithium manganese iron phosphate positive electrode material.
[0022] In some preferred embodiments of the present invention, the total metal salt molar concentration can also be selected to be 1.5 mol / L, 2.0 mol / L, or 2.5 mol / L.
[0023] In some preferred embodiments of the present invention, the soluble phosphate compound in step 1) is one or more of diammonium hydrogen phosphate, ammonium dihydrogen phosphate or phosphoric acid, the soluble divalent manganese salt is one or more of manganous sulfate, manganous nitrate or manganous chloride, and the soluble divalent iron salt is one or more of ferrous sulfate, ferrous nitrate or ferrous chloride.
[0024] In some preferred embodiments of the present invention, the molar ratio of Mn:Fe provided by the soluble divalent manganese salt and the soluble divalent iron salt in step 1) can also be selected as 1.5:1, 2:1, or 3:1; the molar concentration of the total metal salt can also be selected as 1.5 mol / L, 2.0 mol / L, or 2.5 mol / L.
[0025] In some preferred embodiments of the present invention, the amount of the high boiling point organic solvent in step 2) can also be selected to be 2 times, 4 times, 6 times, or 8 times that of deionized water; the ultrasonic treatment time can also be selected to be 5 min, 7 min, 9 min, 11 min, or 13 min; and the ultrasonic frequency can also be selected to be 35 KHz, 40 KHz, or 45 KHz.
[0026] In some preferred embodiments of the present invention, the addition rate of the lithium hydroxide solution in step 3) can also be selected as 3 mL / min, 5 mL / min, 7 mL / min, and 9 mL / min, the concentration of the lithium hydroxide solution can also be selected as 1.5 mol / L, 2.0 mol / L, and 2.5 mol / L, the molar amount of lithium hydroxide can also be selected as 3.03 times, 3.06 times, 3.09 times, and 3.12 times that of the soluble phosphate compound, the stirring rate can also be selected as 100 rpm, 200 rpm, 300 rpm, and 400 rpm, the heating rate can also be selected as 7 ° C / min, 9 ° C / min, 11 ° C / min, and 13 ° C / min, the reaction temperature can also be selected as 150 ° C, 160 ° C, and 170 ° C, and the reaction time can also be selected as 4 h, 6 h, 8 h, and 10 h.
[0027] In some preferred embodiments of the present invention, the mass of the carbon source in step 4) can also be selected as 5%, 10%, or 15% of the mass of the lithium iron manganese phosphate nanoparticle powder, the time of ultrasonic treatment can also be selected as 20 min, 30 min, 40 min, or 50 min, the ultrasonic frequency can also be selected as 35 KHz, 38 KHz, 40 KHz, 42 KHz, 45 KHz, or 48 KHz, the calcination temperature can also be selected as 650 °C, 700 °C, or 750 °C, and the calcination time can also be selected as 5 h, 6 h, or 7 h.
[0028] The present invention also provides lithium manganese iron phosphate nanoparticles prepared by the above preparation method. The nanoparticles are rice-grain-shaped, have good crystallinity, high purity, uniform size distribution, and a particle size of 30-100 nm.
[0029] The present invention also provides a high-voltage lithium manganese iron phosphate positive electrode material prepared by the above preparation method. The positive electrode material has a microsphere porous morphology, a uniform carbon layer coating, good wettability with the electrolyte, and excellent rate performance.
[0030] The lithium manganese iron phosphate described in the present invention is used as a positive electrode material for a lithium ion battery, which can enable the lithium ion battery to not only have excellent specific capacity and rate performance, but also maintain a high discharge voltage and have a higher energy density.
[0031] The following are specific embodiments: Example 1 1) In a 500 mL beaker, weigh 11.53 g of 85% phosphoric acid and add 50 mL of deionized water. Under a nitrogen atmosphere, add 8.54 g of manganous sulfate and 14.04 g of ferrous sulfate to the beaker, stir to dissolve, and then add 0.45 g of ascorbic acid. 2) adding 400 mL of ethylene glycol solvent to the solution obtained in step 1) and subjecting the solution to ultrasonic treatment at an ultrasonic frequency of 40 kHz for 5 min; 3) The mixed solution obtained in step 2) was placed in a normal pressure condensation reflux reactor, 12.84 g of lithium hydroxide was weighed and added to 100 mL of deionized water, and a transparent lithium hydroxide solution was obtained after full dissolution; the lithium hydroxide solution was slowly added to the reactor at a stirring rate of 300 rpm at a rate of 5 mL / min; after the addition was completed, the temperature was increased to 180 ° C at a rate of 5 ° C / min, and the solution was taken out and filtered after condensation reflux reaction for 4 hours, and washed with deionized water for 3 times. The washed solid was placed in a blast drying oven and dried at 60 ° C for 24 hours to obtain lithium iron manganese phosphate nanoparticles LFMP-A1; 4) Take 5.0 g of the granular powder obtained in step 3) and 0.75 g of glucose, disperse them in 100 mL of deionized water, and ultrasonically treat them at an ultrasonic frequency of 40 kHz for 30 min. After spray drying, calcinate them at 650 °C for 6 h in an argon atmosphere to obtain the lithium iron manganese phosphate positive electrode material LFMP / C-A1.
[0032] Example 2 1) In a 500 mL beaker, weigh 11.53 g of 85% phosphoric acid and add 50 mL of deionized water. Under a nitrogen atmosphere, add 8.54 g of manganous sulfate and 14.04 g of ferrous sulfate to the beaker, stir to dissolve, and then add 0.45 g of ascorbic acid. 2) adding 300 mL of ethylene glycol solvent to the solution obtained in step 1) and subjecting the solution to ultrasonic treatment at an ultrasonic frequency of 40 kHz for 5 min; 3) The mixed solution obtained in step 2) is placed in a normal pressure condensation reflux reactor, 12.84 g of lithium hydroxide is weighed and added to 100 mL of deionized water, and a transparent lithium hydroxide solution is obtained after it is fully dissolved; the lithium hydroxide solution is slowly added to the reactor at a stirring rate of 300 rpm at a rate of 5 mL / min; after the addition is completed, the temperature is increased to 170 ° C at a heating rate of 5 ° C / min, and the solution is taken out and filtered after condensation reflux reaction for 6 hours, and washed with deionized water for 3 times. The washed solid is placed in a blast drying oven and dried at 60 ° C for 24 hours to obtain lithium iron manganese phosphate nanoparticles LFMP-A2; 4) Take 5.0 g of the granular powder obtained in step 3) and 0.75 g of glucose, disperse them in 100 mL of deionized water, and ultrasonically treat them at an ultrasonic frequency of 40 kHz for 30 min. After spray drying, calcinate them at 650 °C for 6 h in an argon atmosphere to obtain the lithium iron manganese phosphate positive electrode material LFMP / C-A2.
[0033] Example 3 1) In a 500 mL beaker, weigh 11.53 g of 85% phosphoric acid and add 50 mL of deionized water. Under a nitrogen atmosphere, add 8.54 g of manganous sulfate and 14.04 g of ferrous sulfate to the beaker, stir to dissolve, and then add 0.45 g of ascorbic acid. 2) Add 200 mL of ethylene glycol solvent to the solution obtained in step 1) and perform ultrasonic treatment at an ultrasonic frequency of 40 KHz for 5 min; 3) The mixed solution obtained in step 2) was placed in a normal pressure condensation reflux reactor, 12.84 g of lithium hydroxide was weighed and added to 100 mL of deionized water, and a transparent lithium hydroxide solution was obtained after full dissolution; the lithium hydroxide solution was slowly added to the reactor at a stirring rate of 300 rpm at a rate of 5 mL / min; after the addition was completed, the temperature was increased to 160 ° C at a rate of 5 ° C / min, and the solution was taken out and filtered after condensation reflux reaction for 8 hours, and washed with deionized water for 3 times. The washed solid was placed in a blast drying oven and dried at 60 ° C for 24 hours to obtain lithium iron manganese phosphate nanoparticles LFMP-A3; 4) Take 5.0 g of the granular powder obtained in step 3) and 0.75 g of glucose and disperse them in 100 mL of deionized water, ultrasonically treat them at an ultrasonic frequency of 40 kHz for 30 min, spray dry them, and calcine them at 650 °C for 6 h in an argon atmosphere to obtain the lithium iron manganese phosphate positive electrode material LFMP / C-A3.
[0034] Example 4 1) In a 500 mL beaker, weigh 11.53 g of 85% phosphoric acid and add 50 mL of deionized water. Under a nitrogen atmosphere, add 8.54 g of manganous sulfate and 14.04 g of ferrous sulfate to the beaker, stir to dissolve, and then add 0.45 g of ascorbic acid. 2) adding 400 mL of ethylene glycol solvent to the solution obtained in step 1) and subjecting the solution to ultrasonic treatment at an ultrasonic frequency of 40 kHz for 5 min; 3) The mixed solution obtained in step 2) is placed in a normal pressure condensation reflux reactor, 12.84 g of lithium hydroxide is weighed and added to 100 mL of deionized water, and a transparent lithium hydroxide solution is obtained after full dissolution; the lithium hydroxide solution is slowly added to the reactor at a stirring rate of 200 rpm at a rate of 5 mL / min; after the addition is completed, the temperature is increased to 180 ° C at a heating rate of 5 ° C / min, and the solution is taken out and filtered after condensation reflux reaction for 4 hours, and washed with deionized water for 3 times. The washed solid is placed in a blast drying oven and dried at 60 ° C for 24 hours to obtain lithium iron manganese phosphate nanoparticles LFMP-A4; 4) Take 5.0 g of the granular powder obtained in step 3) and 0.75 g of glucose, disperse them in 100 mL of deionized water, and ultrasonically treat them at an ultrasonic frequency of 40 kHz for 30 min. After spray drying, calcinate them at 650 °C for 6 h in an argon atmosphere to obtain the lithium iron manganese phosphate positive electrode material LFMP / C-A4.
[0035] Example 5 1) In a 500 mL beaker, weigh 11.53 g of 85% phosphoric acid and add 50 mL of deionized water. Under a nitrogen atmosphere, add 8.54 g of manganous sulfate and 14.04 g of ferrous sulfate to the beaker, stir to dissolve, and then add 0.45 g of ascorbic acid. 2) adding 400 mL of propylene glycol solvent to the solution obtained in step 1) and subjecting the solution to ultrasonic treatment at an ultrasonic frequency of 40 kHz for 5 min; 3) The mixed solution obtained in step 2) was placed in a normal pressure condensation reflux reactor, 12.84 g of lithium hydroxide was weighed and added to 100 mL of deionized water, and a transparent lithium hydroxide solution was obtained after full dissolution; the lithium hydroxide solution was slowly added to the reactor at a stirring rate of 300 rpm at a rate of 5 mL / min; after the addition was completed, the temperature was increased to 180 ° C at a rate of 5 ° C / min, and after condensation reflux reaction for 4 h, the solution was taken out and filtered, and washed with deionized water for 3 times. The washed solid was placed in a blast drying oven and dried at 60 ° C for 24 h to obtain lithium iron manganese phosphate nanoparticles LFMP-A5; 4) Take 5.0 g of the granular powder obtained in step 3) and 0.75 g of glucose, disperse them in 100 mL of deionized water, and ultrasonically treat them at an ultrasonic frequency of 40 kHz for 30 min. After spray drying, calcinate them at 650 °C for 6 h in an argon atmosphere to obtain the lithium iron manganese phosphate positive electrode material LFMP / C-A5.
[0036] Example 6 1) Weigh 11.62 g of ammonium dihydrogen phosphate in a 500 mL beaker and add 50 mL of deionized water. Under a nitrogen atmosphere, add 9.99 g of manganous chloride and 10.04 g of ferrous chloride to the beaker, stir to dissolve, and then add 0.4 g of ascorbic acid. 2) adding 400 mL of propylene glycol solvent to the solution obtained in step 1) and subjecting the solution to ultrasonic treatment at an ultrasonic frequency of 40 kHz for 5 min; 3) The mixed solution obtained in step 2) is placed in a normal pressure condensation reflux reactor, 12.84 g of lithium hydroxide is weighed and added to 100 mL of deionized water, and a transparent lithium hydroxide solution is obtained after full dissolution; the lithium hydroxide solution is slowly added to the reactor at a stirring rate of 300 rpm at a rate of 5 mL / min; after the addition is completed, the temperature is increased to 180 ° C at a rate of 5 ° C / min, and the solution is taken out and filtered after condensation reflux reaction for 4 hours, and washed with deionized water for 3 times. The washed solid is placed in a blast drying oven and dried at 60 ° C for 24 hours to obtain lithium iron manganese phosphate nanoparticles LFMP-A6; 4) Take 5.0 g of the granular powder obtained in step 3) and 0.75 g of glucose, disperse them in 100 mL of deionized water, and ultrasonically treat them at an ultrasonic frequency of 40 kHz for 30 min. After spray drying, calcinate them at 650 °C for 6 h in an argon atmosphere to obtain the lithium iron manganese phosphate positive electrode material LFMP / C-A6.
[0037] Comparative Example 1 1) In a 500 mL beaker, weigh 11.53 g of 85% phosphoric acid and add 50 mL of deionized water. Under a nitrogen atmosphere, add 8.54 g of manganous sulfate and 14.04 g of ferrous sulfate to the beaker, stir to dissolve, and then add 0.45 g of ascorbic acid. 2) Add 100 mL of ethylene glycol solvent to the solution obtained in step 1) and perform ultrasonic treatment at an ultrasonic frequency of 40 KHz for 5 min; 3) The mixed solution obtained in step 2) was placed in a normal pressure condensation reflux reactor, 12.84 g of lithium hydroxide was weighed and added to 100 mL of deionized water, and a transparent lithium hydroxide solution was obtained after full dissolution; the lithium hydroxide solution was slowly added to the reactor at a stirring rate of 300 rpm at a rate of 5 mL / min; after the addition was completed, the temperature was increased to 130 ° C at a rate of 5 ° C / min, and after condensation reflux reaction for 4 h, the solution was taken out and filtered, and washed with deionized water for 3 times. The washed solid was placed in a blast drying oven and dried at 60 ° C for 24 h to obtain lithium iron manganese phosphate nanoparticles LFMP-B1; 4) Take 5.0 g of the granular powder obtained in step 3) and 0.75 g of glucose, disperse them in 100 mL of deionized water, and ultrasonically treat them at an ultrasonic frequency of 40 kHz for 30 min. After spray drying, calcinate them at 650 °C for 6 h in an argon atmosphere to obtain the lithium iron manganese phosphate positive electrode material LFMP / C-B1.
[0038] Comparative Example 2 1) In a 500 mL beaker, weigh 11.53 g of 85% phosphoric acid and add 50 mL of deionized water. Under a nitrogen atmosphere, add 8.54 g of manganous sulfate and 14.04 g of ferrous sulfate to the beaker, stir to dissolve, and then add 0.45 g of ascorbic acid. 2) adding 100 mL of propylene glycol solvent to the solution obtained in step 1) and subjecting the solution to ultrasonic treatment at an ultrasonic frequency of 40 kHz for 5 min; 3) The mixed solution obtained in step 2) is placed in a normal pressure condensation reflux reactor, 12.84 g of lithium hydroxide is weighed and added to 100 mL of deionized water, and a transparent lithium hydroxide solution is obtained after full dissolution; the lithium hydroxide solution is slowly added to the reactor at a stirring rate of 300 rpm at a rate of 5 mL / min; after the addition is completed, the temperature is increased to 130 ° C at a heating rate of 5 ° C / min, and after condensation reflux reaction for 4 hours, the solution is taken out and filtered, and washed with deionized water for 3 times. The washed solid is placed in a blast drying oven and dried at 60 ° C for 24 hours to obtain lithium iron manganese phosphate nanoparticles LFMP-B2; 4) Take 5.0 g of the granular powder obtained in step 3) and 0.75 g of glucose, disperse them in 100 mL of deionized water, and ultrasonically treat them at an ultrasonic frequency of 40 kHz for 30 min. After spray drying, calcinate them at 650 °C for 6 h in an argon atmosphere to obtain the lithium iron manganese phosphate positive electrode material LFMP / C-B2.
[0039] Comparative Example 3 1) Weigh 11.62 g of ammonium dihydrogen phosphate in a 500 mL beaker and add 50 mL of deionized water. Under a nitrogen atmosphere, add 9.99 g of manganous chloride and 10.04 g of ferrous chloride to the beaker, stir to dissolve, and then add 0.4 g of ascorbic acid. 2) adding 100 mL of propylene glycol solvent to the solution obtained in step 1) and subjecting the solution to ultrasonic treatment at an ultrasonic frequency of 40 kHz for 5 min; 3) The mixed solution obtained in step 2) is placed in a normal pressure condensation reflux reactor, 12.84 g of lithium hydroxide is weighed and added to 100 mL of deionized water, and a transparent lithium hydroxide solution is obtained after full dissolution; the lithium hydroxide solution is slowly added to the reactor at a stirring rate of 300 rpm at a rate of 5 mL / min; after the addition is completed, the temperature is increased to 130 ° C at a heating rate of 5 ° C / min, and after condensation reflux reaction for 4 hours, the solution is taken out and filtered, and washed with deionized water for 3 times. The washed solid is placed in a blast drying oven and dried at 60 ° C for 24 hours to obtain lithium iron manganese phosphate nanoparticles LFMP-B3; 4) Take 5.0 g of the granular powder obtained in step 3) and 0.75 g of glucose, disperse them in 100 mL of deionized water, and ultrasonically treat them at an ultrasonic frequency of 40 kHz for 30 min. After spray drying, calcinate them at 650 °C for 6 h in an argon atmosphere to obtain the lithium iron manganese phosphate positive electrode material LFMP / C-B3.
[0040] Comparative Example 4 This comparative example is a conventional hydrothermal method; 1) In a 100 mL beaker, weigh 3.46 g of 85% phosphoric acid and add 30 mL of deionized water. Under a nitrogen atmosphere, add 2.56 g of manganous sulfate and 4.21 g of ferrous sulfate to the beaker, stir to dissolve, and then add 0.14 g of ascorbic acid. 2) Weigh 3.86 g of lithium hydroxide and add it to 30 mL of deionized water. After fully dissolving, a transparent lithium hydroxide solution is obtained. Under a stirring rate of 500 rpm, the lithium hydroxide solution is slowly added to the mixed solution obtained in step 1) at a rate of 5 mL / min, and stirred for 15 min. The obtained suspension is poured into a 100 mL polytetrafluoroethylene reactor, reacted at 180 ° C for 12 h, and then the solution is taken out and filtered. The solution is washed with deionized water for 3 times. The washed solid is placed in a blast drying oven and dried at 60 ° C for 24 h to obtain lithium iron manganese phosphate nanoparticles LFMP-B4. 3) 5.0 g of the granular powder obtained in step 3) and 0.75 g of glucose were dispersed in 100 mL of deionized water, and ultrasonically treated at an ultrasonic frequency of 40 kHz for 30 min. After spray drying, the mixture was calcined at 650 °C for 6 h in an argon atmosphere to obtain the lithium iron manganese phosphate positive electrode material LFMP / C-B4.
[0041] Comparative Example 5 This comparative example is a conventional solvothermal method; 1) In a 100 mL beaker, weigh 1.73 g of 85% phosphoric acid and add 30 mL of ethylene glycol. Under a nitrogen atmosphere, add 1.28 g of manganous sulfate and 2.11 g of ferrous sulfate to the beaker, stir to dissolve, and then add 0.07 g of ascorbic acid. 2) Weigh 1.93 g of lithium hydroxide and add it to 30 mL of ethylene glycol. After fully dissolving, a transparent lithium hydroxide solution is obtained. Under a stirring rate of 500 rpm, the lithium hydroxide solution is slowly added to the mixed solution obtained in step 1) at a rate of 5 mL / min, and stirred for 15 min. The obtained suspension is poured into a 100 mL polytetrafluoroethylene reactor, reacted at 180 ° C for 12 h, and then the solution is taken out and filtered. The solution is washed with deionized water for 3 times, and the washed solid is placed in a blast drying oven and dried at 60 ° C for 24 h to obtain lithium iron manganese phosphate nanoparticles LFMP-B5. 3) 5.0 g of the granular powder obtained in step 3) was dispersed with 0.75 g of glucose in 100 mL of deionized water, and ultrasonically treated at an ultrasonic frequency of 40 kHz for 30 min. After spray drying, the mixture was calcined at 650 °C for 6 h in an argon atmosphere to obtain the lithium iron manganese phosphate positive electrode material LFMP / C-B5.
[0042] Experimental Example 1 X-ray diffraction (XRD) characterization analysis was performed on the lithium iron manganese phosphate nanoparticles LFMP-A1, LFMP-A2, LFMP-A3 prepared in Example 1, Example 2, and Example 3, and the lithium iron manganese phosphate nanoparticles LFMP-A1 prepared in Comparative Example 1. The results are as follows: Figure 1 shown.
[0043] Depend on Figure 1 It can be seen that the powder diffraction peaks of the lithium iron manganese phosphate nanoparticles LFMP-A1, LFMP-A2, and LFMP-A3 prepared in Example 1, Example 2, and Example 3 all correspond to the standard olivine-type lithium iron manganese phosphate, and the peaks are symmetrical and sharp, indicating that the lithium iron manganese phosphate nanoparticles prepared by the present invention are pure phase, and there are no other miscellaneous items in the system or the impurity content is extremely low; however, the diffraction peak intensity corresponding to the lithium iron manganese phosphate nanoparticles LFMP-B1 prepared in Comparative Example 1 is low, and a small amount of lithium phosphate impurity phase is present.
[0044] Experimental Example 2 The lithium iron manganese phosphate nanoparticles LFMP-A1 prepared in Example 1 and the lithium iron manganese phosphate nanoparticles LFMP-B1 prepared in Comparative Example 1 were observed by scanning electron microscope (SEM). Figure 2 and Figure 3 shown.
[0045] Depend on Figure 2 It can be seen that the lithium iron manganese phosphate nanoparticles LFMP-A1 prepared in Example 1 are in the shape of rice grains, with a particle size of 30-100 nm and a uniform particle size distribution; Figure 3 It can be seen that the lithium iron manganese phosphate nanoparticles LFMP-B1 prepared in Comparative Example 1 are still in the shape of rice grains, but the particle size of a single particle is relatively large, ranging from 100 to 300 nm, and many small particles are filled between the large particles.
[0046] Experimental Example 3 The lithium iron manganese phosphate positive electrode material LFMP / C-A1 prepared in Example 1 and the lithium iron manganese phosphate positive electrode material LFMP / C-B1 prepared in Comparative Example 1 were subjected to X-ray diffraction (XRD) characterization analysis. The results are as follows: Figure 4 shown.
[0047] Depend on Figure 4It can be seen that the powder diffraction peak of the lithium iron manganese phosphate positive electrode material LFMP / C-A1 prepared in Example 1 corresponds to the standard olivine-type lithium iron manganese phosphate, indicating that the lithium iron manganese phosphate prepared by the present invention is a pure phase of the positive electrode material, and there are no other miscellaneous items in the system or the impurity content is extremely low. The lithium iron manganese phosphate positive electrode material LFMP / C-B1 prepared in Comparative Example 1 also presents a standard diffraction peak, indicating that the diffusion of metal elements occurs during the calcination process, thereby causing the impurity phase in the product to disappear or the content is significantly reduced.
[0048] Experimental Example 4 The lithium iron manganese phosphate positive electrode material LFMP / C-A1 prepared in Example 1 and the lithium iron manganese phosphate positive electrode material LFMP / C-B1 prepared in Comparative Example 1 were observed by scanning electron microscope (SEM). Figure 5 and Figure 6 shown.
[0049] Depend on Figure 5 and Figure 6 It can be seen that the lithium iron manganese phosphate positive electrode materials LFMP / C-A1 and LFMP / C-B1 prepared in Example 1 and Comparative Example 1 are both composed of secondary microspheres formed by primary particles, and the size of the primary particles is not significantly increased compared with their respective precursor lithium iron manganese phosphate particles, indicating that the lithium iron manganese phosphate material has good coating of the carbon layer during high-temperature sintering.
[0050] Experimental Example 5 The lithium iron manganese phosphate positive electrode material LFMP / C-A1 prepared in Example 1 of the present invention and the lithium iron manganese phosphate positive electrode material LFMP / C-B1 prepared in Comparative Example 1 were used as the positive electrode of the lithium-ion battery to assemble a CR2032 button half-cell, the negative electrode was a metal lithium sheet, and the battery was charged and discharged using the Xinwei system.
[0051] 1. Preparation of button cells: The lithium manganese iron phosphate cathode material, Super P and polyvinylidene fluoride (PVDF) were dispersed in N-methylpyrrolidone (NMP) solvent at a mass ratio of 8:1:1 to form a uniform slurry, which was then coated on a carbon-containing aluminum foil current collector and dried overnight in a vacuum oven at 80 °C. A circular electrode with a diameter of 12 mm was cut out using a punching machine. Finally, a CR2032 button cell was assembled in an argon-filled glove box using Celgard 2500 membrane as a separator, a metal lithium sheet as a negative electrode, and 1 mol / L LiPF6 / dimethyl carbonate (DMC) / ethyl carbonate (EMC) / ethylene carbonate (EC) (volume ratio 1:1:1) as an electrolyte.
[0052] Among them, the battery using the lithium iron manganese phosphate positive electrode material LFMP / C-A1 prepared in Example 1 as the battery positive electrode is test battery 1, and the battery using the lithium iron manganese phosphate positive electrode material LFMP / C-B1 prepared in Comparative Example 1 as the battery positive electrode is test battery 2.
[0053] 2. Performance testing and results (1) Test battery 1 and test battery 2 were subjected to constant current charge and discharge tests at a 2C rate, with a voltage range of 2.0-4.5 V (vs. Li + / Li), the results are as follows Figure 7 shown.
[0054] Depend on Figure 7 As shown in the discharge curves of LFMP / C-A1 and LFMP / C-B1, there are two pairs of charge-discharge platforms near 4.1 V and 3.45 V, corresponding to Mn 2+ / Mn 3+ and Fe 2+ / Fe 3+ However, the discharge curve of LFMP / C-B1 shows a rapid decrease in the working voltage. 3+ The discharge voltage of the battery is reduced to about 3.65 V. Although the specific capacity is still considerable, the battery energy density is reduced. In the discharge curve of LFMP / C-A1, Mn 3+ The voltage platform is maintained very stably, allowing the battery to maintain a high discharge voltage and thus have a higher energy density.
[0055] (2) Test battery 1 and test battery 2 were charged and discharged at currents of 0.2C, 0.5C, 1C, 2C, 5C, and 10C (1C = 170 mAh / g), respectively. The results are as follows: Figure 8 shown.
[0056] Depend on Figure 8 It can be seen that the discharge specific capacity of test battery 1 at 0.2C, 0.5C, 1C, 2C, 5C, and 10C rates is 150.42 mAh g −1 、146.62 mAh g −1 , 142.68 mAh g −1 、138.04 mAh g −1 、129.92 mAh g −1 , 121.88 mAh g −1 The discharge specific capacities of test battery 2 at 0.2C, 0.5C, 1C, 2C, 5C, and 10C rates are 148.85 mAh g −1 、144.44 mAh g −1, 139.21 mAh g −1 、131.96 mAh g −1 、115.37 mAh g −1 , 95.05 mAh g −1 .
[0057] It can be seen from the above test results that test battery 1 and test battery 2 have similar discharge specific capacities at low rates, which indicates that the physical phases of the lithium iron manganese phosphate positive electrode material LFMP / C-A1 prepared by Example 1 and the lithium iron manganese phosphate positive electrode material LFMP / C-B1 prepared by Comparative Example 1 have high purity, but with the increase of the charge and discharge rate, the difference in discharge specific capacity between the two becomes larger. Compared with test battery 2, test battery 1 has better rate performance. This is because the primary particles constituting LFMP / C-A1 are finer, and Li + The diffusion path is shorter.
[0058] Experimental Example 6 According to the experimental method in the above-mentioned experimental example 5, the lithium iron manganese phosphate positive electrode material LFMP / CA prepared in Examples 1-6 and the lithium iron manganese phosphate positive electrode material LFMP / CB prepared in Comparative Examples 1-5 were used as lithium-ion battery positive electrodes to assemble test cells, and then constant current charge and discharge tests were performed at a 2C rate, and the voltage range was selected to be 2.0-4.5 V (vs. Li + / Li), test the average discharge voltage of manganese in lithium manganese iron phosphate positive electrode material, the results are shown in Table 1; The particle size of the lithium iron manganese phosphate nanoparticles LFMP / CA prepared in Example 1-6 and the lithium iron manganese phosphate particles LFMP-B prepared in Comparative Example 1-5 were tested using a particle size tester. The results are shown in Table 1. Table 1 Particle size and average discharge voltage of the materials obtained in Examples 1-6 and Comparative Examples 1-5 sample Particle size D50 / nm Average voltage / V Example 1 47.3 3.98 Example 2 73.4 3.95 Example 3 86.9 3.93 Example 4 69.8 3.95 Example 5 51.6 3.97 Example 6 97.3 3.92 Comparative Example 1 153.5 3.86 Comparative Example 2 163.2 3.84 Comparative Example 3 237.1 3.75 Comparative Example 4 541.3 3.57 Comparative Example 5 173.2 3.84 As can be seen from Table 1, the particle size of the lithium iron manganese phosphate nanoparticles prepared by the preparation method of the present invention can be maintained in the nanoscale range of 30-100 nm, and the average discharge voltage of manganese in the lithium iron manganese phosphate positive electrode material synthesized using it as a precursor is greater than 3.9 V; in a pure hydrothermal system, although the single yield is high, the size of the obtained lithium iron manganese phosphate particles is large, and the discharge voltage of the positive electrode material is significantly reduced; in a pure organic solvent system, due to the solubility of the initial raw materials, the total concentration of the materials in the reaction process is limited, the single yield is low, and the size of the obtained lithium iron manganese phosphate particles is also large.
[0059] In summary, it should be noted that the above is only a preferred embodiment of the present invention and does not overly limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, for those skilled in the art, they can still make some simple deductions, replacements, or equivalent replacements for some of the technical features of the technical solutions recorded in the aforementioned embodiments without departing from the concept of the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high voltage lithium manganese iron phosphate positive electrode material, characterized in that: The following steps are involved: 1) Under inert atmosphere, a soluble phosphate compound, a soluble divalent manganese salt and a soluble divalent iron salt are added to deionized water at a molar ratio of P: (Mn+Fe) = 1:1, stirred until completely dissolved, and then an appropriate amount of an antioxidant is added to obtain a mixed solution with a total metal salt molar concentration of 1-3 mol / L; 2) adding 1-10 times the volume of deionized water into the mixed solution obtained in step 1), and subjecting the mixture to ultrasonic treatment; 3) placing the mixed solution obtained in step 2) in a normal pressure condensation reflux reactor, slowly adding a lithium hydroxide solution with a concentration of 1-3 mol / L into the reactor, stirring at a rate of 50-500 rpm, heating the reactor to 140-180°C at a heating rate of 5-15°C / min, keeping the temperature and condensing reflux for reaction for 2-12 hours, and after the reaction is completed, filtering out the solid product, washing, and drying to obtain lithium manganese iron phosphate nanoparticle powder; 4) The lithium manganese iron phosphate nanoparticle powder prepared in step 3) is dispersed with a carbon source in a solvent, subjected to ultrasonic treatment, spray-dried, and calcined at a high temperature under the protection of an inert gas to obtain a lithium manganese iron phosphate positive electrode material.
2. The method for preparing a high voltage lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The soluble phosphate compound in step 1) is one or more of diammonium hydrogen phosphate, ammonium dihydrogen phosphate or phosphoric acid, the soluble divalent manganese salt is one or more of manganous sulfate, manganous nitrate or manganous chloride, the soluble divalent iron salt is one or more of ferrous sulfate, ferrous nitrate or ferrous chloride, and the molar ratio of Mn:Fe provided by the soluble divalent manganese salt and the soluble divalent iron salt is 1-4:
1.
3. The method for preparing a high voltage lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The antioxidant in step 1) is ascorbic acid or citric acid, and the amount of the antioxidant added is 0.5-5% of the total mass of the metal salt.
4. The method for preparing a high voltage lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In the step 2), the high boiling point organic solvent is one of ethylene glycol, propylene glycol, diformate or sulfolane.
5. The method for preparing a high voltage lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The ultrasonic treatment time in step 2) is 3-15 min, and the ultrasonic frequency is 30-50 KHz.
6. The method for preparing a high voltage lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In the step 3), lithium hydroxide solution is added to the mixed solution at a molar ratio of Li:P = 3-3.15:1, and the addition rate of the lithium hydroxide solution is 1-10 mL / min.
7. The method for preparing a high voltage lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In step 4), the carbon source is one of glucose, sucrose, phenolic resin or starch, the mass of the carbon source is 1%-20% of the mass of the lithium manganese iron phosphate nanoparticle powder, and the solvent is water or ethanol.
8. The method for preparing a high voltage lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In the step 4), the ultrasonic treatment time is 10-60 min, the ultrasonic frequency is 30-50 KHz, the high temperature calcination temperature is 600-800° C., and the calcination time is 4-8 h.
9. A high voltage lithium manganese iron phosphate positive electrode material, characterized in that: Prepared by the method according to any one of claims 1 to 8.
10. An application of the high voltage lithium iron manganese phosphate positive electrode material as claimed in claim 9, characterized in that: Used to prepare the positive electrode of lithium-ion batteries.
Citation Information
Patent Citations
Preparation method of pure-phase high-crystallinity lithium iron phosphate
CN101891181A
Positive electrode material of lithium ion battery and preparation method thereof
CN104953118A
Preparation method for ferric manganese phosphate intermediate and lithium ferric manganese phosphate / carbon composite material
CN105244497A
Preparation method for lithium manganese phosphate / graphene / carbon nanocomposite
CN105449178A
Preparation method of carbon coated lithium manganese iron phosphate
CN107768613A
Cited By
Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof
CN120834151A